Global warming and its mitigation through forestry and agroforestry - Dhillon, R.S.; Wuehlisch, George von; ., Ajit (Indian Journal of Agroforestry, 2020)
Rising level of atmospheric CO2 and consequent global warming is evident. Global surface temperature have already increased by 0.8Â°C over the 20th century and is projected to increase by 1.4-5.8Â°C during the twenty-first century. The global warming will continue till atmospheric concentrations of the major greenhouse gases are stabilized. Among them, CO2 is chiefly responsible and is expected to account for about 60% of the warming over the next century.This study reviews advances on causes and consequences of global climate change and its impact on nature and society. Forests and agroforestry have tremendous potential to mitigate the global warming. Agroforestry as carbon sinks is expected to play a multifunctional role including food production, source of energy and fodder, biodiversity conservation, yield of goods and services to the society as well as mitigation of the impact of climate change. The review highlights the different management and research strategies in forestry and agroforestry to mitigate the global warming.